2007
DOI: 10.1093/eurheartj/ehm339
|View full text |Cite
|
Sign up to set email alerts
|

Pacemaker current (If) in the human sinoatrial node

Abstract: I(f) is functionally expressed in human SAN and probably contributes to pacemaking in human SAN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
171
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(198 citation statements)
references
References 41 publications
22
171
1
3
Order By: Relevance
“…35,39 SAN dysfunction commonly occurs in the setting of heart failure and arterial hypertension but also is a genetic disease. Because HCN1 is expressed in the human SAN, 3,40,41 this channel may be added to the list of candidate genes associated with human SAN dysfunction. Mutations in HCN1 could be well tolerated and thus could be relevant for human disease.…”
Section: Discussionmentioning
confidence: 99%
“…35,39 SAN dysfunction commonly occurs in the setting of heart failure and arterial hypertension but also is a genetic disease. Because HCN1 is expressed in the human SAN, 3,40,41 this channel may be added to the list of candidate genes associated with human SAN dysfunction. Mutations in HCN1 could be well tolerated and thus could be relevant for human disease.…”
Section: Discussionmentioning
confidence: 99%
“…This modulation explains the stronger diastolic depolarization slope (DD slope) and the increase in pacing rhythm in response to adrenaline. By contrast, acetylcholine decreases the cAMP levels in the SAN, leading to a smaller current at the same voltage (left-shift of the activation curve), a weaker DD slope and bradycardia [42] . The β accessory subunit MiRP1 changes the activation kinetics of the current in opposite ways depending on the HCN isoform.…”
Section: Membrane or Voltage Clock Modelmentioning
confidence: 92%
“…These variations result from notable interspecies differences in the dynamics and contributions of the calcium handling proteins, in the density of each current, and their regulation. Very few studies, however, have reported data from single cells that were dissociated from an excised human SAN [42,110] . Each of the studies was performed with isolated cells from a single SAN, but it was possible to compare a few electrophysiological parameters with rabbit cells.…”
Section: Human Embryonic Stem Cell-derived Cardiomyocytes: a Model Fomentioning
confidence: 99%
“…In analogy to rabbit SAN, the small (or absent) I K1 current may be the reason for the more positive resting membrane potential in human SAN cells. 8 Indirectly, this supports pacemaking. The HCN4 mRNA abundance was much lower in human compared with rabbit SAN, 4 and this is in good agreement with the 3 to 4 times smaller I f amplitude found in humans.…”
Section: Article P 1562mentioning
confidence: 92%